PENERAPAN MEDIA GAMBAR DAN KATA BANTU UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA KELAS III TAHUN AJARAN 2012/2013 SDN 3 BUDUAN KECAMATAN SUBOH KABUPATEN SITUBONDO - Eni Kurniawati; Hasan Muchtar Fauzi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2013)
Learning to write poetry is considered very difficult for third-grade students of SD Negeri 3 Buduan District of Suboh Situbondo. The value of learning achieved by students in the writing of poetry has not met the minimum criteria in SD Negeri 3 Buduan is 60. The number of students who have not experienced a 60% mastery learning and mastery learning which has undergone only 6 children. This study aims to describe the application of media images and words to help improve students' ability to write poetry class III Elementary School 3 Buduan District of Suboh Situbondo and to determine the increase in the ability to write poetry Elementary School third-grade students 3 Buduan District of Suboh Situbondo through the application of media images and said auxiliary. This study used a design of Classroom Action Research (CAR) with a qualitative approach. This study used the draft TOD because of the ability of third grade students of SDN 3 Buduan in writing poetry and yet still not achieve mastery learning. Data were collected by observation, field notes, interviews, tests and documentation. The results obtained in this study indicate that the number of students who experienced prasiklus completeness study only 33.3%. In prasiklus stage, the teacher has not given action on learning to write poetry. But after being given the action in the first cycle, students who received ≤60 value reached 61.1%. While the results of the ability to write poetry in the second cycle shows the number of students who achieve a minimum completeness criteria reached 77.7%. The act of learning to write poetry using media images and helpers managed to improve the ability of third-grade students to write poetry SDN 3 Buduan. It can be seen on the control aspect of the content suitability for using media images and words to help students be able to write poetry in accordance with drawings and words that help exists